Employing Internal Auditor Geometry Thinking to Enhance Company Value - mohamed ali wahab, asaad; talib elchemari, mushtaq (Journal of Research in Finance and Accounting, 2022)
The aim of the research is to test the effect of employing the engineering thinking of the internal auditor in geometry the value of the company in the light of the accounting information environment, through a sample of (194) internal auditors selected from among selected economic sectors (banking, industrial, service, other) in order to achieve a comprehensive picture of the answers In order to test the research hypotheses, the researchers used a set of statistical methods for descriptive and inferential analysis, including (weighted arithmetic mean, standard deviation) and (simple correlation coefficient, simple and multiple regression), in addition to testing the impact of the accounting information environment through testing its interactive role. . The research reached a number of conclusions, the most important of which is that internal auditors have a high skill to arrange their thinking, and that internal auditors are natural people, they are more understanding of the impact of social and cultural factors than other factors regarding the value of the company, and there is a positive and moral correlation between the engineering thinking of the internal auditor and the value of the company.